Analisis Kemampuan Kognitif Peserta Didik: (Studi pada Lembaga Pendidikan MI al-Kautsar Yogyakarta) - Habibah Mu'minah (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2020)
Humans are one of the living things that experience development in every time, one of the most important aspects of development is the cognitive aspect. Cognitive development is a comprehensive development that is related to the ability to think, such as the ability to remember, reason, imagine, and creative. Cognitive development is the stages of changes that occur in everyday life to be able to understand, manage information, solve problems, and know something. Every child can develop their knowledge, meaning that the knowledge possessed by each child can be formed by each user interaction with the environment that is continuous and always changing. With the development of cognitive abilities, children can easily master extensive knowledge. Children's knowledge is formed gradually in line with the experience of the information found. Cognitive development involves expanding the horizon of stimuli that are close to and into more distant space.